AN ANNOTATED TRANSLATION OF SIMPLE WAYS TO MAKE YOUR FAMILY HAPPY - Herlina Lindaria Simanjuntak (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
This research is an annotated translation. The object of the research is an English book Simple Ways To Make Your Family Happy. The purposes of this study are: (1) to attain factual information concerning the problems faced by the researcher in translating the source text, and (2) to give plausible solution to the difficulties. The researcher uses the introspective and retrospective methods in conducting this annotated translation research. The result of the study covered two main points. First, the finding revealed that from the twenty five most difficult problems, five were in the form of words, eight were phrases, five were idioms, three were clauses, and four were sentences. Theseannotations of hers indicated that during the course of her translation, she had difficulties with them. Second, those difficulties were solved by referring to the relevant theories of translation and the theories of English and Indonesian languages.Keywords: Annotated, Translation, your, family, happy.